Production of Biodiesel From Microalgae Using Ultrasound - Vikinesh, Mariappan (2013)
Biodiesel is a clean-burning environmentally friendly fuel. Since the combustion of biodiesel releases carbon dioxide into the air that is taken out of the air by plants, it is called carbon neutral. In fact, it releases less greenhouse gas than diesel and it is biodegradable so it does not cause great harm to the environment if there is a spill. The ultrasound has been proved that low intensity of sonication can improve the fermentation process instead of high intensity sonication. The objective of the study is to investigate the production of lipid from microalgae by applying ultrasound, determine kinetic parameters and determine the rate of production of lipid. Nannochloropsis sp. will be used in this study and cultured in f/2 medium. The cell will be treated with ultrasound where the culture will be pump to ultrasound and recycled back to the medium. The impact of different power and regiment of ultrasound sonication will be investigated. Duty cycles of 10%, 20% and, 40% will be used. The outcome is ultrasound can enhance the production of lipid from microalgae Nannochloropsis sp. The optimum power and intensity is selected by observing the cell reduction. The optimum intensity for this project is 10.2 watt/cm2. Nannochloropsis sp. gives a better result in 10% of duty cycle with the intensity of 10.2 watt/cm2. The power and the intensity is determined after observe the absorbance after sonication at various power and amplitude. The 20% and 40% sonication did not give a good result because it seems to give a intense condition for the microalgae to grow.